2010
DOI: 10.1366/000370210792434404
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Microstructured Silicon Wafers as Internal Reflection Elements in Attenuated Total Reflection Fourier Transform Infrared Spectroscopy

Abstract: A novel internal reflection element (IRE) for attenuated total reflection Fourier transform infrared (ATR-FT-IR) spectral acquisition is introduced and applied for several surface-sensitive measurements. It is based on microstructured double-side-polished (100) silicon wafers with v-shaped grooves of {111} facets on their backside. These facets of the so-called "microstructured single-reflection elements" (mSRE) are formed by a crystal-oriented anisotropic wet etching process within a conventional wafer struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…In an earlier study [1], the change in surface chemistry in the form of oxygenated or nonoxygenated Si hydrides on the SiO 2 or Si(100) surface during a hydrogen fluoride etch of a thin native oxide was observed. In this study, similar surface species during CMP could not be observed.…”
Section: Determination Of Film Thickness From In Situ Ftir Spectramentioning
confidence: 95%
See 2 more Smart Citations
“…In an earlier study [1], the change in surface chemistry in the form of oxygenated or nonoxygenated Si hydrides on the SiO 2 or Si(100) surface during a hydrogen fluoride etch of a thin native oxide was observed. In this study, similar surface species during CMP could not be observed.…”
Section: Determination Of Film Thickness From In Situ Ftir Spectramentioning
confidence: 95%
“…figure 1). Details about the fabrication process of these wafers, called microstructured single reflection elements (mSRE) [1], and the basics of the ATR-FTIR spectroscopy [3,4] are described elsewhere.…”
Section: Microstructured Single Reflection Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Furthermore, microstructured single-bounce ATR crystals make use of the easy access to Si fabrication, while allowing to extending the IR transmission of Si beyond multireflection elements. 13 All these emerging systems can be further exploited by custom-made and fit-forpurpose scientific instrumentation. Since its introduction in the 1980s, 3D-priniting has evolved into a versatile platform for rapid manufacturing of customized parts made of metals, ceramics and polymers.…”
mentioning
confidence: 99%
“…DOI: 10.1002/smll.202002290 the fabrication of inverted silicon pyramids for various applications, e.g., for atomic force microcopy (AFM) tip fabrication, photovoltaics, or infrared spectroscopy. [4][5][6] Adding surfactants to KOH allows for changing the typical wet etch taper. [7] Metal films have been used for highly selective etching of diamond.…”
mentioning
confidence: 99%